TERMINATION OF CAPITAL COMPANY’S ACTIVITY BEYOND THE REACH AT ITS LEGAL ADDRESS - Kaļva, Aldis (Administrative and Criminal Justice, 2019)
The paper explores termination of the activity of a capital company if it cannot be reached at its registered office. For almost ten years, there is a grapple with a problem that limited liability companies are absent at their legal addresses or the consent of the owners of the property is forged to register the legal address of the company. Regulations have already been amended for several times with the aim of eliminating unfair practices, however, with little success up to now. Recently, in 2017, the amendments to the Commercial Law have come into force, which provides for the elimination of a capital company that will not be accessible at its legal address; therefore it is important to study the particular issue to determine the impact of the aforementioned amendments on the registration of a front company. As the aim of the paper was set to discover and analyse the problem of capital companies’ simplified liquidation if they cannot be reached at their legal addresses. Systemic, dogmatic and comparative methods of studying and analyzing normative acts and court rulings have been used in the paper.